2004
DOI: 10.1021/ma0498621
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Casting Solvents on the Formation of Inverted Phase in Block Copolymer Thin Films

Abstract: Previously, an inverted phase (the minority blocks comprising the continuum phase) was found in solution-cast block copolymer thin films. In this study, the effect of casting solvents on the formation of inverted phase has been studied. Two block copolymers, poly(styrene-b-butadiene) (SB) (M w = 73 930 Da) and poly(styrene-b-butadiene-b-styrene) (SBS) (M w = 140 000 Da), with comparable block lengths and equal polystyrene (PS) weight fraction (∼30 wt %) were used. The copolymer thin films were cast from differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
101
2
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(108 citation statements)
references
References 58 publications
3
101
2
2
Order By: Relevance
“…More recently, solvent-annealing and the control of the solvent evaporation rate have been found to create ordered structures in a thin film of a similar diblock copolymer, polystyrene-b-polybutadiene (PS-b-PB). [33][34][35] Our approach is simpler: templates are created from the non-equilibrium in-frozen structure of the copolymer thin films after spin-casting. (46) (symmetric copolymer) ultrathin films with increasing thickness.…”
Section: Preparation Of Copolymer Templatesmentioning
confidence: 99%
“…More recently, solvent-annealing and the control of the solvent evaporation rate have been found to create ordered structures in a thin film of a similar diblock copolymer, polystyrene-b-polybutadiene (PS-b-PB). [33][34][35] Our approach is simpler: templates are created from the non-equilibrium in-frozen structure of the copolymer thin films after spin-casting. (46) (symmetric copolymer) ultrathin films with increasing thickness.…”
Section: Preparation Of Copolymer Templatesmentioning
confidence: 99%
“…[21][22][23]30 Thus, from the calculation of interaction parameters, it is seen that CHX used in this study is a θ-solvent for PS blocks and a good solvent for PBD blocks while HX is a selective solvent for only PBD blocks. Hence, CHX can provide a higher degree of swelling for PBD blocks than for PS blocks.…”
Section: Methodsmentioning
confidence: 82%
“…It is noted that some research groups reported that inversion of the contrast between PS and PBD, where the PS phase and PBD phase became dark and bright, respectively, could occur when the microscope was fulfilled at moderate tapping. 29,30 However, because our AFM experiments were operated at hard tapping, the glassy PS phase and rubbery PBD phase in phase mode of our AFM images appear as bright and dark regions, respectively.…”
Section: Methodsmentioning
confidence: 93%
See 2 more Smart Citations